2011
DOI: 10.1111/j.1445-2197.2010.05642.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fatigue on surgeon performance and surgical outcomes: a systematic review

Abstract: There is little evidence, as yet, to inform the issue of the effect of fatigue on surgical performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 42 publications
2
68
0
2
Order By: Relevance
“…In accordance with this finding, previous findings by Koslowsky et al have shown that the effect of sleep deprivation on cognitive performance in laparoscopies only becomes apparent after 36-40 h of sleep deprivation [3]. Strum et al, in their review, showed that in most trials measuring clinical surgical performance there was no effect of fatigue, and that sleep deprivation has a greater effect on the surgical performance of younger rather than senior residents [12].…”
Section: Discussionsupporting
confidence: 64%
“…In accordance with this finding, previous findings by Koslowsky et al have shown that the effect of sleep deprivation on cognitive performance in laparoscopies only becomes apparent after 36-40 h of sleep deprivation [3]. Strum et al, in their review, showed that in most trials measuring clinical surgical performance there was no effect of fatigue, and that sleep deprivation has a greater effect on the surgical performance of younger rather than senior residents [12].…”
Section: Discussionsupporting
confidence: 64%
“…Fatigue and sleep deprivation may increase the risk of malpractices. [1][2][3] There are several reports from different surgical fields reporting worse outcomes for surgeries performed during after-hours or nighttime. [4][5][6][7] There are also reports from different coun- outcomes has hardly been evaluated because in modern anesthesia practice, adverse outcomes are relatively low.…”
Section: Introductionmentioning
confidence: 99%
“…It was previously reported by Sturm et al that less experienced surgeons are more affected by fatigue than more experienced surgeons, both in terms of actual surgical performance and simulated performance. 13 While we do show in our cohort of relatively inexperienced surgeons that fatigue decreases performance, our findings indicate that the consequences of fatigue were more severe in the experienced residents. In this sense, fatigue acts as an equalizer.…”
Section: Discussionmentioning
confidence: 45%
“…10 However, numerous studies have also been published that indicate surgeon performance is not affected by fatigue. [11][12][13][14][15] Therefore, further investigation is required.…”
Section: Introductionmentioning
confidence: 97%